Components of Brief Alcohol Interventions for Youth in the Emergency Department. Issue 3 (July 2015) - Walton, Maureen A.; Chermack, Stephen T.; Blow, Frederic C.; Ehrlich, Peter F.; Barry, Kristen L.; Booth, Brenda M.; Cunningham, Rebecca M.
Background: Alcohol brief interventions (BIs) delivered by therapists are promising among underage drinkers in the emergency department (ED); however, integration into routine ED care is lacking. Harnessing technology for identification of at-risk drinkers and delivery of interventions could have tremendous public health impact by addressing practical barriers to implementation. The paper presents baseline, within BI session, and posttest data from an ongoing randomized controlled trial (RCT) of youth in the ED. Methods: Patients (ages 14–20) who screened positive for risky drinking were randomized to computer BI (CBI), therapist BI (TBI), or control. Measures included demographics, alcohol consumption (Alcohol Use Disorders Identification Test—Consumption [AUDIT-C]), process questions, BI components (e.g., strengths, tools), and psychological constructs (i.e., importance of cutting down, likelihood of cutting down, readiness to stop, and wanting help). Results: Among 4389 youth surveyed (13.7% refused), 24.0% ( n = 1053) screened positive for risky drinking and 80.3% ( n = 836) were enrolled in the RCT; 93.7% ( n = 783) completed the posttest. Although similar in content, the TBI included a tailored, computerized workbook to structure the session, whereas the CBI was a stand-alone, offline, Facebook-styled program. As compared with controls, significant increases were found at posttest for the TBI in "importance to cut down" and "readiness to stop" and for the CBI in "importance and likelihood to cut down." BI components positively associated with outcomes at posttest included greater identification of personal strengths, protective behavioral strategies, benefits of change, and alternative activities involving sports. In contrast, providing information during the TBI was negatively related to outcomes at posttest. Conclusions: Initial data suggest that therapist and computer BIs are promising, increasing perceived importance of reducing drinking. In addition, findings provide clues to potentially beneficial components of BIs. Future studies are needed to identify BI components that have the greatest influence on reducing risky drinking behaviors among adolescents and emerging adults.